2016
DOI: 10.1088/1674-1056/25/7/077503
|View full text |Cite
|
Sign up to set email alerts
|

Structural stability at high pressure, electronic, and magnetic properties of BaFZnAs: A new candidate of host material of diluted magnetic semiconductors

Abstract: The layered semiconductor BaFZnAs with the tetragonal ZrCuSiAs-type structure has been successfully synthesized. Both the in-situ high-pressure synchrotron x-ray diffraction and the high-pressure Raman scattering measurements demonstrate that the structure of BaFZnAs is stable under pressure up to 17.5 GPa at room temperature. The resistivity and the magnetic susceptibility data show that BaFZnAs is a non-magnetic semiconductor. BaFZnAs is recommended as a candidate of the host material of diluted magnetic sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…the "111" type Li(Zn,Mn)As、 "122" type (Ba,K)(Zn,Mn) 2 As 2 and "1111" type (La,Ca)(Zn,Mn)SbO, which are named by the chemical ratio of their parent phases. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Among these new DMSs, the ThCr 2 Si 2 type (Ba,K)(Zn,Mn) 2 As 2 has a Curie temperature (Tc) up to 230 K which marks the current reliable record Tc for DMSs where ferromagnetism is mediated by carriers. [12][13] The (Ba,K)(Zn,Mn) 2 As 2 is believed to be one of milestone materials for the research of DMSs.…”
Section: Introductionmentioning
confidence: 99%
“…the "111" type Li(Zn,Mn)As、 "122" type (Ba,K)(Zn,Mn) 2 As 2 and "1111" type (La,Ca)(Zn,Mn)SbO, which are named by the chemical ratio of their parent phases. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Among these new DMSs, the ThCr 2 Si 2 type (Ba,K)(Zn,Mn) 2 As 2 has a Curie temperature (Tc) up to 230 K which marks the current reliable record Tc for DMSs where ferromagnetism is mediated by carriers. [12][13] The (Ba,K)(Zn,Mn) 2 As 2 is believed to be one of milestone materials for the research of DMSs.…”
Section: Introductionmentioning
confidence: 99%
“…High quality polycrystalline BaFZnAs was reported to be a semiconductor in our previous work31. Figure 4 shows the temperature dependence of resistivity of BaFZnAs, indicating a semiconductor behavior.…”
Section: Resultsmentioning
confidence: 72%
“…1a, is the same as that of the parent compound BaFZnAs31. It is found that the majority of peaks in the XRD pattern can be well indexed to main phase, except for some tiny peaks from the nonmagnetic impurity phase of BaF 2 .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…g . “111” type Li(Zn,Mn)As and Li(Zn,Mn)P, “122” type (Ba,K)(Zn,Mn) 2 As 2 and “1111” type (La,Ca)(Zn,Mn)SbO, have been discovered to overcome the aforementioned difficulties 716 . In these new types of diluted ferromagnetic semiconductors spin is doped via isovalent substitution of (Zn 2+ ,Mn 2+ ), while charge is provided by off-stoichiometry of Li in the “111” type diluted ferromagnetic semiconductors or by heterovalent substitution of cations in the “122” and “1111” diluted ferromagnetic semiconductors.…”
Section: Introductionmentioning
confidence: 99%